Provision of Mobile-Diabetic Applications on Knowledge and Compliance with Type II Diabetes Mellitus Outpatient Diet - Mifta Husaadah Alham; Widyana Lakshmi Puspita; Sopiyandi (POLTEKKES KEMENKES PONTIANAK, 2020)
Diabetes mellitus is a disease that threatens global health and most are classified as type 2 diabetes mellitus caused by interactions between factors to the environment. Environmental factors that are expected to increase the risk factors for type 2 diabetes mellitus are not adhering to a diet, changing one's lifestyle, including unbalanced eating habitsThis type of research is a quasi-experimental study with a design using the one group pretest posttest approach. The total sample of 35 people was taken by purposive sampling technique. Pre test was carried out before being given m-diabetic application media and given a post test after being given m-diabetic application media. This study used the Kolmogorov-Smirnov normality test and a different Wilcoxon test.The results showed a significant change in the form of increased knowledge (p = 0,000) and an increase in adherence to a type 2 diabetes mellitus diet (p = 0,000). The conclusion of this study is that there are differences in knowledge after being given m-diabetic application media and there are differences in adherence to the diet type 2 diabetes mellitus. Melitus type II, and further researchers can use an android-based application as an educational medium for sufferers of other diseases.